National Museum of Dentistry exhibition: the future is now! African Americans in dentistry. - Dummett, Clifton O. (National Medical Association, 2003)
Inspired by recently published NDA II: The Story of America's Second National Dental Association and sponsored jointly by the National Dental Association Foundation and the Colgate-Palmolive Company, an historical exhibit on dentistry in the African-American community was one of the celebrations for the Golden Anniversary of the American Academy of the History of Dentistry. This exhibit premiered on Sept. 27, 2002 in the National Museum of Dentistry located on the medical/dental campus of the University of Maryland in Baltimore. The Museum recently became an affiliate of the Smithsonian Institution. Contents of the exhibit were photographs, charts, artifacts, memorabilia, etc. These materials presented an overview of African-American activities in dental education, research, patient care, general practice, dental specialities, military service, and public health. Also included were inter-racial relationships, socioeconomic developments, and participation in civil rights endeavors that played a major role in changing out-dated accepted customs. The exhibit's purpose was to celebrate dentistry's ministrations as a health professional among African Americans in particular and the nation at large over the past two centuries. Respect for and progress of black dentists paralleled that of black physicians who were instrumental in including dentist and pharmacists as equal members in the National Medical Association since the latter's inception in 1895.